INFLUENCE OF A PMBOK-BASED MANAGEMENT MODEL ON THE EFFICIENCY OF FISHERIES ENTERPRISE PROJECTS IN ONG, LIMA - Canales La Rosa, José Alberto (2026)
The aim of the research was to determine the influence of the project management model on the efficiency of fisheries entrepreneurship projects, from the perspective of the PMBOK. The methodology was correlational, quantitative and non-experimental in design. The population consists of staff working in the field of fisheries entrepreneurship projects. It was demonstrated that the project management model influences project efficiency, given that there is a high correlation. Similarly, planning and scheduling, monitoring and control, resource and capacity management, participation and continuous improvement were found to have a direct positive influence on project efficiency.